2013
DOI: 10.1055/s-0032-1328361
|View full text |Cite
|
Sign up to set email alerts
|

Analyse der Venenbewegungen in der Netzhaut von Glaukompatienten

Abstract: Retinal veins in glaucoma eyes demonstrate lower pulse amplitudes than healthy eyes, indicating disturbance in venous outflow and increased intraluminal venous pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In glaucomatous eyes, retinal veins in the immediate vicinity of, as well as away from the optic disc, demonstrated lower pulse amplitudes than in healthy eyes, indicating disturbances in venous outflow and increased intraluminal venous pressure and resistance. [ 14 , 15 ] Morgan et al suggested that such a gradual increase in central retinal vein resistance may be implicated in central retinal vein occlusions, shunt vessels, and ODHs. [ 12 ] In addition, ODH occurs up to 4 times more frequently in normal-tension glaucoma (NTG) than in primary open-angle glaucoma (POAG) patients with baseline intraocular pressure (IOP) of more than 21 mmHg.…”
Section: Introductionmentioning
confidence: 99%
“…In glaucomatous eyes, retinal veins in the immediate vicinity of, as well as away from the optic disc, demonstrated lower pulse amplitudes than in healthy eyes, indicating disturbances in venous outflow and increased intraluminal venous pressure and resistance. [ 14 , 15 ] Morgan et al suggested that such a gradual increase in central retinal vein resistance may be implicated in central retinal vein occlusions, shunt vessels, and ODHs. [ 12 ] In addition, ODH occurs up to 4 times more frequently in normal-tension glaucoma (NTG) than in primary open-angle glaucoma (POAG) patients with baseline intraocular pressure (IOP) of more than 21 mmHg.…”
Section: Introductionmentioning
confidence: 99%
“…RVP was increased in glaucoma [314], and correspondingly, the pulse amplitude in these veins was lower [315]. Eyes with optic disc haemorrhages did not have higher RVP but did have lower retinal arterial pressures in comparison to both the contralateral eyes and eyes of control patients matched for BP [253].…”
Section: Retinal Venous Pressurementioning
confidence: 99%
“…Störungen der Mikrozirkulation mit einem verminderten retinalen, choroidalen und retrobulbären Blutfluss wurden zudem bei Patienten mit Offenwinkelglaukom nachgewiesen [12][13][14][15][16]. Verminderte Pulsamplituden der Netzhautvenen weisen bei Glaukomen auf eine alterierte venöse Mikrozirkulation mit gestörtem Venenabfluss und erhöhtem intraluminalen Druck hin [98].…”
Section: Gefäßeunclassified